WORD SEARCH ULTIMATE GAME TOWARD STUDENT'S VOCABULARY MASTERY OF THE FIFTH GRADE STUDENTS AT MUHAMMADIYAH ELEMENTARY SCHOOL OF METRO - Eva Faliyanti; Arif Irfan Tanjung (Intensive Journal, 2020)
One of the components in English that is very important in understanding when someone is communicating each other is vocabulary. The vocabulary is used to express the ideas. This research was aimed to find out the influence of using word search ultimate game in learning English for student's vocabulary mastery in the 5th of Muhammadiyah Elementary School of Metro. The research was conducted by quantitative methods. The population of the research consisted of 235 students. The research divided into two groups, those are 24 students as the experimental group and 24 students as the control group, the total of the sample consist of 48 students. The research used cluster random sampling technique and an analysis by using t-test formula. The instruments of this research were pre-test and post-test. The result of analysis was indicated that the value of t obtained (6.961) was higher than that of t table (2.06) at the significance level 0.05 and the significance (0.000) was lower than 0.05). It means that there was significant influence toward student’s vocabulary mastery using word search ultimate game of the fifth grade students of Muhammadiyah Elementary School of Metro.